Unconventional Resources Technology Conference 2015
DOI: 10.2118/178653-ms
|View full text |Cite
|
Sign up to set email alerts
|

Data Analytics for Production Optimization in Unconventional Reservoirs

Abstract: Considerable amounts of data are being generated during the development and operation of unconventional reservoirs. Statistical methods that can provide data-driven insights into production performance are gaining in popularity. Unfortunately, the application of advanced statistical algorithms remains somewhat of a mystery to petroleum engineers and geoscientists. The objective of this paper is to provide some clarity to this issue, focusing on: (a) how to build robust predictive models, and (b) how to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The DT method is a supervised ML algorithm which is based on a group of nodes called root, decision, and leaf nodes [66]. Each leaf represents a numeric value for an important independent variable [67]. The SVM model is also a supervised learning method that is used in handling regression and classification problems [67].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The DT method is a supervised ML algorithm which is based on a group of nodes called root, decision, and leaf nodes [66]. Each leaf represents a numeric value for an important independent variable [67]. The SVM model is also a supervised learning method that is used in handling regression and classification problems [67].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Quite good results were shown by the authors of the article [14]; they also investigated various models. But as noted in the article from 476 wells, only 171 have no NaN values.…”
Section: Overfittingmentioning
confidence: 95%
“…In [14] the authors developed a decision procedure to separate good wells from poor performers. For this purpose, the author investigated Wolfcamp well dataset.…”
Section: Recent Boom In Shale Fracturingmentioning
confidence: 99%
“…where p is the number of predictor variables, is the noise terms, it is assumed that noise terms are uncorrelated and have independent and identical normal distributions with mean zero and constant variance [19,25,26]. The noise terms represent some variables that not include but may have contribution to Y.…”
Section: Multiple Linear Regression (Mlr)mentioning
confidence: 99%
“…The aim of SVR is to find a function f (x) that diverge from response y by a value no more than , and in the meantime the function f (x) as even as possible (Figure 2). More details about SVR are described in Al-Azani et al [28], Da Silva et al [29], El-Sebakhy et al [30], Li et al [31] and Schuetter et al [26]. In SVR, the choice of kernel function directly determines the performance of the model, the main kernel functions used in this study are shown as follows:…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%